Design and development of a comprehensive framework to enhance leadership skills in project management - Pablo Delgado-Valencia; Pedro Sánchez-Caimán (Dyna)
This research aimed to design a framework for leadership competence in project management training for industrial engineering professionals at universities in Bogotá, Colombia. Motivated by the observed absence of this competence among recent graduates. The study employed a sequential exploratory design using mixed methods. By characterizing global leadership models in project management theorized by academia and leading organizations, key variables were identified. Diagnosing the leadership competence of students generated relevant data, which were statistically analysed, facilitating academic recommendations and the framework's design. The outcome significantly contributes to the field by providing a functional and generalisable framework for universities in Bogotá, strengthening leadership competence in professional training. This research underscores the complexity and centrality of leadership in project management, highlighting the need for an adaptive and practical framework to guide the education of future professionals with holistic and applicable skills to effectively lead in volatile and ambiguous environments.